ANALISIS LAPORAN KEUANGAN PADA PT BERAU MOTOR PART: ANALISIS LAPORAN KEUANGAN PADA PT BERAU MOTOR PART - Hakim Syaf'rul (ECO-BUILD, 2018)
The purpose of this study was to find out how the financial performance of PT Berau Motor Part in 2015, 2016, and 2017. In this paper using financial ratio analysis tools. Based on the results of the study and discussion of the analysis of financial statements and doing some calculations using financial ratios, among others, liquidity ratio, solvency ratio, activity ratio, and profitability ratio can be concluded that the liquidity ratio of PT Berau Motor Part is in good condition. Where the company is declared healthy and in good condition because it is able to pay off short-term obligations. The solvency ratio of PT Berau Motor Part is in a good condition. Where total debt is still low compared to total assets and total capital. Then it can be interpreted that the company is able to cover its debts with assets and capital. Activity ratio at PT Berau Motor Part is in a bad condition. In the sense that the company has not been effective in using the company's resources. The profitability ratio of PT Berau Motor Part is in a bad condition. Then it can be interpreted that the company has not been able to increase profitability. So the writer draws back this research hypothesis, because the results of the study indicate that the financial performance of PT Berau Motor Part is not fully in good condition.